Soursop fruit (Annona muricata Linn.) consumption does not increase serum potassium levels and not significant in cardiovascular risk improvements of prehypertension subjects - Alatas, Haidar; Sja'bani, Mochammad; Irijanto, Fredie; Mustofa, .; Mukti, Ali Ghufron; Bawazier, Lucky Aziza; Zulaela, Zulaela (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Patients with chronic kidney disease (CKD) tend to have hyperkalemia. They worry about the consumption of fruit for fear of increased serum potassium levels and therefore require a restricted potassium diet. Soursop fruit (Annona muricata Linn.) is believed to be beneficial for CKD and cardiovascular risk. This study was conducted to investigate the effect of soursop fruit supplement consumption on serum potassium levels and cardiovascular risk in prehypertension subjects from Mlati, Sleman District, Yogyakarta Special Region, Indonesia. A total 143 samples that met to the inclusion and exclusion criteria were subsequently randomized into two groups. Group I was given 2 x 100 g/day of soursop and Group II was without soursop. A laboratory examination from both groups was conducted including potassium, total cholesterol, low density lipoprotein (LDL), high density lipoprotein(HDL), and triglyceride levels at weeks 0; 7; and 13. Regular soursop consumption was evaluated every 2 weeks for 3 months. Data analysis was performed using an independent t test, a nonparametric Mann–Whitney test, and a chi-square test. No significantly different in serum potassium levels between the soursop and non-soursop groups at week 7 and 13 (p=0.073 and p=0.108) was observed. Furthermore, no significantly different in total cholesterol (p=0.254 and p=0.932), LDL (p=0.221 and p=0.710), HDL (p=0.400 and p=0.960), triglycerides (p=0.423 and p=0.580) of both groups was also obsereved. However, in subjects with hypercholesterolemia and hypertriglyceridemia, the mean cholesterol and triglyceride levels decreased compared to no soursop consumption at week 7 and 13. In conclusion, consumption of a soursop fruit supplement of 2 x 100 g/day for 13 weeks does not affect the serum potassium levels of prehypertension subjects. Moreover, the consumption of a soursop fruit supplement is not significantly different compared to those without soursoup in improving cardiovascular risk.